Metagenomic Next-Generation Sequencing Is Highly Efficient in Diagnosing Pneumocystis Jirovecii Pneumonia in the Immunocompromised Patients - Wang, Dongsheng; Fang, Shihua; Hu, Xiaowen; Xu, Qixia; Chu, Xinmin; Mei, Xiaodong; Xie, Wang (Frontiers in Microbiology, 2022)
Purposes: To explore the value of metagenomic next-generation sequencing (mNGS) in diagnosing pneumocystis jirovecii pneumonia (PJP) in the immunocompromised patients. Methods: Data of 122 PJP patients in immunosuppressed state and 67 non-PJP patients were collected. The diagnostic efficacy of mNGS was compared with the conventional methods, including Gomori methenamine silver (GMS) staining and serum (1,3)-β-D-glucan (BDG). Changes of anti-microbial therapy for PJP patients based on mNGS results were also reviewed. Results: The diagnostic sensitivity of mNGS to PJP was higher than that of GMS and BDG (100% vs 15% and 74.5%, P < 0.001). The diagnostic specificity (91.0%) was lower than that of GMS (100%), and similar with BDG (89.6%). In addition to P. jirovecii, mNGS revealed co-pathogens like human β-herpesvirus 5, human γ-pesvirus 4, and some other opportunistic pathogens. The reads of mNGS were remarkably higher in BALF than in blood samples. Initial antimicrobial treatment was modified in 89.3% patients based on the mNGS results and 74 cases (60.7 %) were treated with anti-P. jirovecii therapy. Conclusions: mNGS is highly efficient in diagnosing PJP and good at identifying pathogens in mixed infections.